EVALUASI KINERJA DAN EFISIENSI JARINGAN LORAWAN UNTUK APLIKASI IOT DI LINGKUNGAN SUBURBAN - Surya Saputra, Rengga; Pramaita, I Nyoman; Gunantara, Nyoman (Jurnal SPEKTRUM, 2024)
The current era of digitalization is rapidly advancing, especially in the utilization of Internet of Things (IoT) technology for various purposes, including in the transportation and vehicle rental sectors. This research focuses on the application of the LoRaWAN network in supporting the electric scooter rental system in suburban environments, particularly in the Kintamani area. The designed system allows real-time monitoring of electric scooter locations through the integration of GPS modules, and also provides additional security features with an emergency button for urgent situations. The system is also equipped with rental time settings to maximize efficiency in managing electric scooter rentals. LoRaWAN was chosen for its ability to transmit data over long distances with low power consumption, which is highly suitable for suburban areas with wide coverage and limited infrastructure. This research not only evaluates the network's performance in terms of communication but also reviews the system's efficiency in terms of the number of devices that can be connected simultaneously. The evaluation focuses on how optimally this system can be used on a larger scale, especially in supporting the growing needs of IoT. This study provides insights into the potential development of a safer and more efficient IoT-based bike rental system in suburban environments.